2013
DOI: 10.1038/ejcn.2013.58
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding syndrome in children with different clinical aetiology

Abstract: Refeeding syndrome (RFS) is a well-described state of the series of metabolic and biochemical changes that can occur during the feeding of malnourished persons. The shifts in fluids and electrolytes can lead to complications during artificial feeding, which if not recognised and untreated can lead to death. Although the physiology and pathophysiology of RFS is well known, the circumstances under which the RFS appears, clinical manifestations and management of these patients are less clear. There are few publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Mechanical ventilation and inotropic agents were started; however, the patient died 2 days later with multiple‐organ failure 81 . Additional cases of RS in pediatric patients with celiac disease have been described 82,83 …”
Section: Populations Potentially At Risk For Refeeding Syndromementioning
confidence: 94%
“…Mechanical ventilation and inotropic agents were started; however, the patient died 2 days later with multiple‐organ failure 81 . Additional cases of RS in pediatric patients with celiac disease have been described 82,83 …”
Section: Populations Potentially At Risk For Refeeding Syndromementioning
confidence: 94%
“…Agarwal et al reported five pediatric patients [ 7 ]. Recently, Lenicek et al reported another pediatric case [ 8 ]. These patients showed a severely malnourished celiac disease with a BMI of less than 14, a hypophosphatemia, a hypocalcaemia, and a hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , caloric content and osmolality of Terumeal-mini are approximately 1.5 times that of Ensure Liquid. In children, refeeding syndrome may develop without clinical signs, detectable only through laboratory findings [ 10 ]. The total calorie intake of Terumeal-mini at 320 kcal/day was not significantly greater in this patient than the previous calorie intake of 300 kcal/day.…”
Section: Discussionmentioning
confidence: 99%